Vehicle Routing Problem (VRP) Approaches for Waste Collection Optimization: A Systematic Literature Review - Munengsih Bunga; Mochamad Agung Wibowo; Sutikno (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2026)
An effective route is necessary because waste transport is an important part of the urban waste management system. The most popular technique is the Vehicle Routing Problem (VRP) to maximize fleet movement while reducing risk, time, cost, and energy. To identify developments in VRP models in the context of waste transportation, this study used a Systematic Literature Review (SLR), conducted in accordance with PRISMA guidelines, to review 96 articles. The SLR results indicate that VRP models have evolved from basic models such as CVRP and VRPTW to more constraint-rich models such as MTVRP, ARP, risk-aware VRP, EVRP, and multi-objective VRP. Hybrid and metaheuristic algorithms such as ALNS, GA, ACO, and SA have become the most popular in solving this problem due to their ability to handle large problem sizes and high operational complexity. Route planning can now utilize real-time data thanks to the integration of IoT, WSN, and GIS technologies. Overall, these results indicate that VRP research in waste transport is moving towards smarter, more adaptive, and sustainable approaches. These results also enable the development of more contextual models and algorithms in the future.